2008
DOI: 10.1211/jpp.60.1.0015
|View full text |Cite|
|
Sign up to set email alerts
|

Protective effects of hydroxysafflor yellow A on acute and chronic congestive cardiac failure mediated by reducing ET-1, NOS and oxidative stress in rats RETRACTED ARTICLE

Abstract: The present study was conducted to investigate whether hydroxysafflor yellow A (HSYA) has a protective effect on acute and chronic heart failure (AHF/CHF) induced by ligation of the left anterior descending coronary artery for 3 h and 8 weeks, respectively. The rats were divided into the following groups: sham operation, coronary artery ligation (CAL), CAL+HSYA (100 mg kg(-1) by gavage) and CAL+diltiazem (20 mg kg(-1) by gavage). In the AHF model, heart function, as determined by haemodynamic studies and echoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Previous studies have demonstrated that the protective effect of HSYA against LPS-induced acute lung injury was associated with the significant inhibition of p38 MAPK phosphorylation in vitro and in vivo (Song et al, 2013;Sun et al, 2010). He et al (2008) revealed that the non-receptor tyrosine phosphatase Shp2 promotes adipogenesis through the Shp2-p38MAPK-p300-PPARg signaling pathway, by inhibiting the phosphorylation of p38 MAPK and enhancing PPAR-g expression. Consistent with this, the PPAR-g agonist rosiglitazone has been shown to downregulate gonadotropin-releasing hormone-mediated phosphorylation of p38 MAPKs in LbT2 cells (Sakaida et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the protective effect of HSYA against LPS-induced acute lung injury was associated with the significant inhibition of p38 MAPK phosphorylation in vitro and in vivo (Song et al, 2013;Sun et al, 2010). He et al (2008) revealed that the non-receptor tyrosine phosphatase Shp2 promotes adipogenesis through the Shp2-p38MAPK-p300-PPARg signaling pathway, by inhibiting the phosphorylation of p38 MAPK and enhancing PPAR-g expression. Consistent with this, the PPAR-g agonist rosiglitazone has been shown to downregulate gonadotropin-releasing hormone-mediated phosphorylation of p38 MAPKs in LbT2 cells (Sakaida et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that free radicals play an active role in the early events of OGD-R-induced apoptosis (Rawal et al 2004;Shen et al 2004). It has been reported that HSYA, one of the major active chemical component of the yellow color pigments extracted from the safflower, exhibits strong scavenging effects on cytotoxic oxygen radicals (Tian et al 2008;Wei et al 2005;He et al 2008). In the present experiment, OGD-R caused a significant increase in level of MDA, the marker of lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…It exerts a variety of effects upon the cardiovascular system. For example, HSYA inhibits thrombosis and platelet aggregation, improves congestive cardiac failure in rats by suppressing ET-1 and iNOS and reduces oxidative stress in infarcted tissue [23]. HSYA has also been shown to reduce phenylephrine or KCl-induced vasoconstriction and to reduce blood pressure and heart rate [24].…”
Section: Introductionmentioning
confidence: 99%